EDUKASI MELALUI KOMIK “ANAKKU STUNTING” UNTUK PENINGKATAN PENGETAHUAN REMAJA TENTANG BAHAYA NIKAH DINI DALAM UPAYA PENCEGAHAN STUNTING - Khair Anwar, Khalidatul; Wulandari, Hesti; Sarita, Sultina; Asmaidar; Mihora, Dian Putri Ekawati (Poltekkes Kemenkes Kendari, 2025)
Adolescent pregnancy due to early marriage has a negative impact on the health of adolescents and their babies, especially increasing the risk of stunting in children. Therefore, it is important to provide education to adolescents regarding the dangers of this by paying attention to the condition of adolescents as targets. Teenagers today generally prefer something that is varied and not boring, the education/counseling process must be designed with this in mind. The use of the right media can be one of the solutions to increase the interest of adolescents to get health information, one of these media is comics that can increase interest in reading. This service program aims to increase adolescents' knowledge about the dangers of early marriage in stunting prevention through the use of educational comics. The method is by providing education to teenagers through the use of educational comics. The training was conducted within 2 days. The number of trainees is 30 people. The success of the program can be seen from the change in knowledge about the dangers of early marriage in stunting prevention.